Investigating the Impact of Acute and 28-days Oral Exposure to Decaprenyl phosphoryl-β-D-ribose 2’- epimerase (DprE1) Inhibitors on Vital Organ Function in Swiss Albino Mice - Gawad, Jineetkumar; Bonde, Chandrakant; Bonde, Smita; Sharma, Mayank; Suthar, Dinesh; Palkar, Mahesh; Beldar, Vishal; Dhokchawle, Bharat; Raghuwanshi, Vaishali (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background Tuberculosis (TB) is a severe airborne infectious disease caused by Mycobacterium tuberculosis, a contagious bacillus and the second leading cause of mortality. A pivotal obstacle in Tuberculosis (TB) therapy lays in the swift emergence of resilient TB mycobacterial variants during treatment regimens, thereby precipitating the dissemination of Multi-Drug Resistant (MDR-TB) and extensively drug-resistant M. tuberculosis (XDR-TB) strains. The objective of present study to evaluate toxicity of synthesized novel DprE1 inhibitors. Materials and Methods Research is currently directed towards discovering novel targets possessing advantageous microbiological characteristics for treating tuberculosis. Key compounds such as imidazo-pyridine, pyrazine, pyrimidine and quinazoline are pivotal elements of therapeutic significance in this endeavour. Despite this, there remains a scarcity of drugs developed for this infectious disease. Decaprenyl-phosphoryl-β-D-ribose-2-Epimerase (DprE1) is a crucial enzyme involved in arabinose biosynthesis, a component of the mycobacterium cell wall. We had synthesized series of compounds with basic nucleus imidazo-pyridine, quinazoline-4- carboxaminde and benzothiazole substituted; these compounds were subjected for in vitro antitubercular assay (Risazurine microtiter assay) and DprE1 enzyme specific studies. Three compounds (each from series) were selected here for toxicity studies. Activity of these selected compounds was 5i-0.8 μmol/L, 5g-1.01 μmol/L and 3a-1.27 μmol/L. Initial screening for acute and subacute toxicity involved albino mice weighing between 25-31 g, following OECD 423 guidelines. Results The research determined that a dose of 300 mg/kg was safe, with no abnormalities observed in the animals on the 7th, 14th and 28th days of the study. Conclusion Necropsies revealed normal average weights and vital organs (heart, lungs, liver and kidney) in all groups compared to the control group. Histopathological examinations did not indicate any abnormalities such as swelling, elongation, shrinking, deformation, or cell death in the vital organs studied.
Keywords: Toxicity; Antitubercular Agents; DprE1 Inhibitors; NCEs